2010
DOI: 10.3174/ajnr.a1988
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intraobserver Agreement in CT Characterization of Nonaneurysmal Perimesencephalic Subarachnoid Hemorrhage

Abstract: BACKGROUND AND PURPOSE:The perimesencephalic pattern of SAH as seen on unenhanced CT is associated with significantly better outcomes when compared to an aneurysmal pattern of SAH. The aim of this study was to determine the degree of inter-and intraoberver agreement for characterization of the NAPH as seen on unenhanced CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…In 1 study, the overall interobserver and intraobserver agreement for nonaneurysmal perimesencephalic hemorrhage was good, but there was still a level of disagreement among observers, which suggests that clinicians should be cautious when deciding whether to pursue follow-up imaging. 108 In another study, 109 a negative CTA result reliably excluded aneurysms when head CT showed the classic perimesencephalic SAH pattern or no blood. Digital subtraction angiography (DSA) was indicated if there was a diffuse aneurysmal pattern of aSAH, and repeat delayed DSA was required if the initial DSA findings were negative, which led to the detection of a small aneurysm in 14% of cases.…”
Section: Clinical Manifestations and Diagnosis Of Asahmentioning
confidence: 99%
“…In 1 study, the overall interobserver and intraobserver agreement for nonaneurysmal perimesencephalic hemorrhage was good, but there was still a level of disagreement among observers, which suggests that clinicians should be cautious when deciding whether to pursue follow-up imaging. 108 In another study, 109 a negative CTA result reliably excluded aneurysms when head CT showed the classic perimesencephalic SAH pattern or no blood. Digital subtraction angiography (DSA) was indicated if there was a diffuse aneurysmal pattern of aSAH, and repeat delayed DSA was required if the initial DSA findings were negative, which led to the detection of a small aneurysm in 14% of cases.…”
Section: Clinical Manifestations and Diagnosis Of Asahmentioning
confidence: 99%
“…The authors concluded that patients with pretruncal PSAH and presentations compatible with a nonaneurysmal etiology can undergo initial evaluation with CTA alone and do not require follow-up imaging [20]. This meta-analysis is limited by inconsistent definitions of PSAH used in the constituent studies, and clinical implementation of such recommendations is limited by inter-observer variability in terms of characterizing SAH patterns [21,22]. Regardless, extending such recommendations to patients with quadrigeminal PSAH is premature.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the criteria of some studies permit small amounts of intraventricular hemorrhage2 4 6 7 9 11 12 26 while others do not 5 8 10 13 25. Similarly, some criteria permit extension of blood to the posterior part of the anterior interhemispheric and/or basal part of the Sylvian fissures1 2 6–9 12 while others do not 10 11 13 14 24 25. The subjective language used in many criteria also contributes to inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although imaging evaluation for a ruptured aneurysm remains mandatory in patients with perimesencephalic subarachnoid hemorrhage (PSAH), identification of this pattern has clinical utility in terms of choosing whether or not to perform follow-up imaging, the type of imaging performed (ie, CT vs catheter angiography), as well as for prognosis and patient reassurance 5 7–10. However, the existing literature is limited by inconsistent definitions of a PSAH pattern, as well inter-observer variability in characterizing the SAH pattern 4 11…”
Section: Introductionmentioning
confidence: 99%